Kinematic Characteristics of Male Runners With a History of Recurrent Calf Muscle Strain Injury - Christopher Bramah; Stephen J Preece; Niamh Gill; Lee Herrington (North American Sports Medicine Institute, 2021)
# Background Calf muscle strain injuries are a common running injury affecting male runners and are known to have high reoccurrence rates. Currently, limited evidence exists investigating factors associated with this injury with no previous study investigating the running kinematics of male runners with a history of repeat calf muscle strain injuries. # Purpose To investigate whether male runners with a history of repeat calf muscle strain injury demonstrate differences in stance phase running kinematics when compared to healthy controls. # Study Design Case-control investigation # Level of Evidence 3b # Methods Stance phase kinematics were compared between 15 male runners with a history of calf muscle strain injury and 15 male control participants during treadmill running at 3.2m/s. Independent t-tests were used to compare differences in stance phase kinematic parameters between groups and effect sizes were calculated using Cohen's d. # Results The group with a history of calf muscle strain injury demonstrated a significant 2.1⁰ and 3.1⁰ increase in contralateral pelvic drop and anterior pelvic tilt during mid stance. In addition, this group exhibited longer stance times and a more anterior tilted pelvis, flexed hip and a greater distance between the heel and centre of mass at initial contact. Large effect sizes, greater than 0.8, were observed for all differences. No significant differences were observed for ankle and knee joint kinematics between the groups. # Conclusion This is the first study to identify kinematic characteristics associated with recurrent calf muscle strain injury. While it is not possible to determine causality, the observed kinematic differences may contribute to recurrent nature of this injury. Specifically, it is possible that neuromuscular deficits of the hip and calf muscle complex may lead to increased strain on the calf complex. Rehabilitation interventions which focus on addressing pelvis and hip kinematics may reduce the demands placed upon the calf complex and could prove clinically effective.